2018
DOI: 10.1007/s00270-018-2036-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Stent Coating Inhibits Platelet Adhesion on Stent Surfaces: Initial Results In Vitro

Abstract: BackgroundEndovascular stents and flow diverter stents (FDS) have revolutionized the treatment of intradural aneurysms; however, the need for dual anti-platelet treatment (DAPT) limits their use and can cause additional issues. Therefore, there is a need to develop stent coatings that negate the need for DAPT.MethodsTwo different hydrophilic polymer coatings (HPC-I and HPC-II) were used to coat small nickel titanium plates to initially test the hydrophilic properties of these coatings when applied to nickel ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…pHPC is a glycan-based hydrophilic multilayer polymer coating which can be applied to nitinol surfaces. It is designed to mimic the biological properties of the glycocalyx, the coverage that can be found on the luminal surface of the endothelium of the arterial wall, making the coated surface hydrophilic and, consequently, less thrombogenic [4]. pHPC has no pharmaceutical effect, is biocompatible with no evidence of acute inflammatory response, and does not interact with the physical properties of the metallic implant [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pHPC is a glycan-based hydrophilic multilayer polymer coating which can be applied to nitinol surfaces. It is designed to mimic the biological properties of the glycocalyx, the coverage that can be found on the luminal surface of the endothelium of the arterial wall, making the coated surface hydrophilic and, consequently, less thrombogenic [4]. pHPC has no pharmaceutical effect, is biocompatible with no evidence of acute inflammatory response, and does not interact with the physical properties of the metallic implant [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The p48MW (phenox, Bochum, Germany) is a new FDS that has been designed to treat distal aneurysms in vessels with diameters of between 1.75 and 3 mm [3]. Its hydrophilic polymer coating (pHPC, phenox, Bochum, Germany) is a novel glycan-based multilayer polymer that has been shown to have significant anti-thrombogenic properties when tested in vitro [4]. A recently published study concluded that the p48MW HPC appears both safe and efficacious under single antiplatelet therapy (SAPT) using prasugrel in selected cases of unruptured aneurysms [5].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of coated versus uncoated p48 flow diverters using scanning electron microscopy demonstrated minimal adherent platelets on the coated flow diverters compared with a thick layer of adherent platelets on uncoated devices. 7 Individual thrombocytes tended to adhere in the vicinity of defects on the wire surface, but large cell agglomerates were not detected. Further studies comparing the p48 with the p48_HPC in a flow model have also been performed.…”
Section: Patientmentioning
confidence: 98%
“…We have recently shown that the hydrophilic polymer coating (pHPC, registered trademark of Phenox) has anti-thrombogenic properties when tested in vitro [ 26 ], but there is little known about the in vivo biocompatibility of this coating. The purpose of this study was to determine the acute and chronic biocompatibility of the pHPC coating when applied to the pCONUS device.…”
Section: Introductionmentioning
confidence: 99%